Payne-Sperb-Stakgold Type Inequality for a Wedge-Like Membrane - Abir Sboui (International Journal of Analysis and Applications, 2022)
For a bounded domain contained in a wedge, we give a new Payne-Sperb-Stakgold type inequality for the solution of a semi-linear equation. The result is isoperimetric in the sense that the sector is the unique extremal domain.